1997
DOI: 10.1136/ard.56.8.463
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoking and rheumatoid arthritis severity

Abstract: Objectives-Cigarette smoking may influence rheumatoid arthritis (RA) disease incidence and may have direct biological eVects on the lungs and systemically. This study sought to determine if cigarette smoking is associated with RA disease severity. Methods-Clinical evaluations of patients seen in the University of Iowa rheumatology and orthopaedic ambulatory clinics were conducted. A letter of interest was mailed to 1701 patients who were first assigned an ICD-9-CM diagnostic code for RA in one of these clinics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
151
3
11

Year Published

2001
2001
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 262 publications
(175 citation statements)
references
References 38 publications
(12 reference statements)
10
151
3
11
Order By: Relevance
“…Del Rincon et al (21) examined cardiovascular events and reported significant associations with both diabetes and hypertension. Smoking is an established risk factor for atherosclerosis and is also associated with the development and severity of RA (47,(55)(56)(57). In our study, we demonstrated, by univariate analysis, that a history of smoking prior to the RA incidence date increased the risk of cardiovascular death in a dose-dependent manner, but the association was no longer significant when other cardiovascular variables were considered.…”
Section: Discussionmentioning
confidence: 50%
“…Del Rincon et al (21) examined cardiovascular events and reported significant associations with both diabetes and hypertension. Smoking is an established risk factor for atherosclerosis and is also associated with the development and severity of RA (47,(55)(56)(57). In our study, we demonstrated, by univariate analysis, that a history of smoking prior to the RA incidence date increased the risk of cardiovascular death in a dose-dependent manner, but the association was no longer significant when other cardiovascular variables were considered.…”
Section: Discussionmentioning
confidence: 50%
“…The association of smoking with development and severity of RA was documented almost 30 years ago [10] and confirmed in many subsequent studies [11][12][13][14][15][16][17][18][19][20][21]. A recent dose-response meta-analysis (encompassing 4,552 RA patients) reported relative risks of 1.26 and 1.96 for the associations of RA with smoking histories of 1-10 and >20 pack years respectively [19].…”
Section: Smoking and Ramentioning
confidence: 80%
“…There is evidence from cross-sectional studies that smoking is associated with longterm erosive damage [2][3][4][5] , although some longitudinal studies failed to find an association 6,7 . However, the longitudinal studies have been carried out mainly in patients with earlier disease.…”
Section: To the Editormentioning
confidence: 99%